Geology - Geologic Setting of the Nickel Occurrences on Jumbo Mountain, Washington (Mining Engineerng, Mar 1960 pg 272) - J. W. Mills (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
In 1956 the discovery of nickel on Jumbo Mountain, Snohomish County, Washington, focused attention on this part of the Cascade Range, far more renowned for its timber than for its mineral resources. Hand specimens assaying as high as 13 pct Ni encouraged Discovery Mines Inc. of Mount Vernon, Wash., to stake 12 claims in Township 31 North, Range 9 East of the Willamette Meridian. The property was leased to Climax Molybdenum Co. in January 1957. Trenching, sampling, and geologic studies were carried out during the late summer of 1957 when most of the snow had disappeared. Although the deposits are only about four miles south of the logging town of Darrington and about two miles. as the crow flies, southeast of the end of a good gravel road from that town, all camp supplies and equipment were air-dropped, owing to the extremely rugged nature of the terrain. GEOLOGY The rocks of Jumbo Mountain comprise a series of folded Tertiary sediments forming a belt one half to three quarters of a mile wide, trending northwest about parallel to the strike of the beds. This belt is sandwiched between two extensive in-trusives—gabbro on the northeast and quartz dio-rite on the southwest—and has been intruded by dikes of fresh and serpentinized dunite. Shear zones follow many of the dunite-sedimentary rock contacts, and in these the nickel mineralization is concentrated. A few transverse faults offset the sediments and ultrabasics. Sedimentary Rocks: Two kinds of quartzite make up the greater part of the sedimentary section. One is dark purplish gray, very fine-grained, and thin-bedded; the other is light gray to white, medium-grained, and well-bedded. Locally the light-colored quart lites contain grit and conglomerate horizons, rich in pebbles of white chert and very fine-grained quartzite. Intercalations of dark argillites near the summit of the mountain give many of the cliffs a striking banded appearance. Dark gray to black, aphanitic, thin-bedded argillites occur throughout the entire sedimentary belt. Beds vary from a few inches to a few tens of feet thick and some, near the summit, contain numerous fossile (willow?) leaves. Only the thicker beds were mapped. The sediments are quite fresh on the northeastern side of the belt and become more metamorphosed (hornfelsed) toward the southwestern side. Brown biotite is present in the metasediments in increasing amounts as the quartz diorite is approached. Near the intrusion, porphyroblasts of plagioclase, up to 1 in. across, testify to the soaking of sedimentary rocks by solutions emanating from the quartz diorite. Most of the sediments mapped lie along the southwestern limb of an anticline, the axis of which follows the crest of the mountain and plunges at a low angle to the northwest.